PERAN KEWIRAUSAHAAN DALAM PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PENGEMBANGAN UMKM - Muh Irshan Sachrir; Ade Vidya Eryanti K (Universitas Ichsan Sidenreng Rappang, 2026)
Community economic empowerment is an important effort to improve the welfare and independence of society. Micro, Small, and Medium Enterprises have a strategic role in supporting economic growth and creating employment opportunities for the community. However, the development of these enterprises still faces several challenges such as limited access to capital, low managerial capacity, and limited utilization of technology. This study aims to analyze the role of entrepreneurship in community economic empowerment through the development of Micro, Small, and Medium Enterprises. This research uses a qualitative approach with a descriptive method. The research data were obtained through observation, interviews, and documentation involving Micro, Small, and Medium Enterprise actors and related stakeholders in community business development. The results show that entrepreneurship plays an important role in improving business capacity, creating product innovation, and expanding market opportunities. The development of Micro, Small, and Medium Enterprises also has a positive impact on increasing community income, creating employment opportunities, and strengthening local economic activities. Therefore, strengthening entrepreneurial capacity and sustainable policy support are essential factors in promoting community economic empowerment through the development of Micro, Small, and Medium Enterprises.